The uplift capacity of single-plate helical pile in shallow dense sand including the influence of installation. (May 2020) - Wang, Le; Zhang, Puyang; Ding, Hongyan; Tian, Yinghui; Qi, Xin
Abstract: The helical pile has been used to resist the tension for a long time. However, the prediction of the uplift capacity of helical piles including the influence of installation is still a challenge in design. Based on the change in stress according to Mohr-Coulomb failure criterion, a simple theoretical method has been developed, which can calculate the uplift capacity of shallow pre-embedded circular plate anchors and the uplift capacity of helical piles installed by torque and compression. In order to analyse the influence of installation process of a single-plate helical pile on its uplift capacity and verify the theoretical model, a series of model tests have been conducted in dense saturated sand. The single-plate helical piles with different out diameters of helixes have been installed with different installation speeds, and then, the single-plate helical piles have been moved up monotonically. The test results show that the installation speed and the size of the out diameter of the helix have significant influence on the uplift capacity of the helical piles, and the results of the theoretical method have a good fit with the test results. Using this simple theoretical method, the designer can easily predict the uplift capacities of helical piles, which includes the influence of installation. Highlights: The prediction of the uplift capacity of helical piles including the influence of installation. A serious of model tests with different helix diameters are conducted in dense saturated sand. The installation speed and the size of helix out diameter have significant influence on the uplift capacity of helical piles.